War resistance : . War Resisters' International bulletin
(1923) - (1926) titled: War Resisters' International bulletin. - (1926) - (1962) titled: The war resister. - German ed.: Widerstand gegen den Krieg. Vierteljährliche Zeitschrift ... (ZO 6211). - French ed.: Résistance à la guerre. Organe trimestriel ... (ZO 6211). - Esperanto ed.: Militrezisto (ZO 6211).